2020
DOI: 10.1515/sjpain-2020-0112
|View full text |Cite
|
Sign up to set email alerts
|

Pain management programmes via video conferencing: a rapid review

Abstract: ObjectivesDuring the current COVID-19 pandemic, healthcare has been transformed by the rapid switch from in person care to use of remote consulting, including video conferencing technology. Whilst much has been published on one-to-one video consultations, little literature exists on use of this technology to facilitate group interventions. Group pain management programmes are a core treatment provided by many pain services. This rapid review aimed to identify the extent of use of video conferencing technology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 23 publications
0
22
0
1
Order By: Relevance
“…These include patient concerns about losses in supportive peer relationships and patient–therapist relationships, 10 lack of resources encompassing both IT equipment and exercise equipment, unfamiliarity with video-communication systems and the need for clinician training and infrastructure investment. 5 During the project, we were able to resolve many of these issues with input from all staff engaged in PMP delivery and the patients. An important factor in finding these solutions was the selection of an appropriate software programme with functionalities that could meet patient and clinician needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include patient concerns about losses in supportive peer relationships and patient–therapist relationships, 10 lack of resources encompassing both IT equipment and exercise equipment, unfamiliarity with video-communication systems and the need for clinician training and infrastructure investment. 5 During the project, we were able to resolve many of these issues with input from all staff engaged in PMP delivery and the patients. An important factor in finding these solutions was the selection of an appropriate software programme with functionalities that could meet patient and clinician needs.…”
Section: Discussionmentioning
confidence: 99%
“…A recent rapid review of PMPs delivered via video-conferencing 5 identified three papers up until April 2020 and determined that video-conferencing for PMPs was feasible, but there was little guidance on how to develop and deliver these. In this article, we describe how this goal was achieved at our institution, using a quality improvement (QI) approach and service user involvement.…”
Section: Introductionmentioning
confidence: 99%
“…The experience accumulated in the management of patients with cancer pain during the pandemic suggests that many episodes of NP-BTcP are not reported during periodic consultations but are recorded by the patient in the monitoring system [29]. In other words, the impact on quality of life is always present, but both patients and clinicians tend to underestimate the effect [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Access in rural and remote areas may be limited. Pain services via videoconference may be possible but are untested 61…”
Section: What Are the Management Options For Non-specific Low Back Pain?mentioning
confidence: 99%